Produtividade e composição química de pastagem de Tifton 85 inoculada com Azospirillum brasilense associada à fertilização nitrogenada - Silva, Aline Rodrigues (2019)
Tifton 85 bermudagrass have been widely used in tropical and subtropical regions. Due to its high forage yield, the fertility requirement of Tifton 85 is also high. The inoculation with Azospirillum brasilense is an alternative to reduce nitrogen fertilizers and costs, consequently. However, the effects of inoculation in tropical grasses are still little knew. The aim of this study was to evaluate the productivity, pasture characteristics and chemical composition of Tifton 85 bermudagrass, inoculated with Azospirillum brasilense and associated to nitogen fertilizer. The study evaluated four nitrogen levels (0, 100, 200 and 300 kg ha-1), inoculated or not, under cutting conditions. The experimental design was completely randomized, in a factorial arrangement, with two qualitative levels (inoculated with Azospirillum brasilense or uninoculated) and four quantitative (nitrogen doses), with three replications (plots). Botanical and morphological composition, leaf/steam ratio, chemical composition and forage yield were evaluated. Inoculation raised the herbage yield in all pastures, but did not affect the chemical composition of forage. Increasing nitrogen fertilizers is associated with herbage yield and crude protein concentration. Neutral detergent fibers and total digestible nutrients were not affected by inoculation or nitrogen fertilization.